The Variation of Disulfides in the Progression of Type 2 Diabetes Mellitus - Ergin, Merve; Aydin, Cevdet; Yurt, Emine Feyza; Cakir, Bekir; Erel, Ozcan (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aim The purpose of this study was to examine thiol-disulfide balance in patients with type 2 diabetes mellitus.Methods This study included 32 subjects with known type 2 diabetes mellitus without complications, 30 patients with type 2 diabetes mellitus with complications, 28 newly diagnosed patients with type 2 diabetes mellitus, and 45 healthy individuals. Thiol-disulfide profile tests were quantified in all groups.Results Compared to the control group, patients in each of the diabetic groups had significantly lower native and total thiol levels, higher disulfide levels, and higher disulfide/native thiol and disulfide/total thiol ratios (p<0.05 for all). Disulfide levels were significantly lower in the newly diagnosed group than in other diabetic groups (p<0.05). There were significant associations between glycemic parameters and thiol-disulfide tests (p<0.05).Conclusions A disequilibrium between thiol-disulfide pairs occurs in patients with type 2 diabetes mellitus, and a gradual increase to disulfide levels may contribute to the disease’s severity. Deteriorated thiol-disulfide homeostasis may be relevant to the pathophysiology of type 2 diabetes mellitus.
Keywords: disulfide; oxidative stress; thiol-disulfide homeostasis; type 2 diabetes mellitus